Kobiety, które przyczyniły się do umocnienia relacji Polski z Nową Zelandią - Siekiera, Joanna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Bilateral relations between Poland and New Zealand do not have a long history nor major trade or geopolitical strategic directions. However, friendly and deeply grounded in the consciousness of the New Zealand public opinion relations require better analysis also in Poland. The important role of Poles and New Zealand women in the process of establishing and then strengthening ties between Warsaw and Wellington cannot to be underestimated. What appears important, in the whole history of diplomacy, women have never had such huge impact on creating politics or interests of their nations. Though, such situation did actually take place since the beginning of the Polish-New Zealand relations constituting. These women, both as consuls, ambassadors and diplomatic representatives’ wife, as well as ordinary citizens have showed their patriotic attitude in the partner country. Their efforts to depict tradition and culture of the other country contributed to create a good image of Poland in the Pacific, as well as New Zealand in the Central Europe, which already has its impact on the opening of new missions, the abolition of visas or export growth
Keywords: polityka; Nowa Zelandia; kobiety; dyplomacja; stosunki polsko-nowozelandzkie; stosunki dyplomatyczne